Analisis Ketersediaan Air Bersih dalam Mendukung Ketahanan Kota di Kota Bandar Lampung - Mia Ermawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The level of availability of water in Bandar Lampung cannot be separated from changes in land cover conditions in Bandar Lampung which are very dynamic. Thus, in order to analyze the availability of water for supporting the resilience city, it is necessary to project the land cover of the city of Bandar Lampung. In this study, the analysis used is spatial analysis and analysis of the coefficient ecosystem services (KJE) for the provision of water. Spatial analysis is used as the basis for all input and output processes to process land cover and ecoregion data through an overlay process. In identifying environmental services providing of water, the first step is to map the land cover and ecoregion conditions in Bandar Lampung. Based on the results of the research that has been carried out, it is known that in the period 2010 to 2021 the land cover of Bandar Lampung experienced land changes and experienced water is deficit in 2021, as well as the projection results in 2031 where the water availability of Bandar Lampung is dominated by low class and very low.